PENGARUH PROFITABILITY, LIQUIDITY, DAN FAKTOR LAINNYA TERHADAP AGRESIVITAS PAJAK - Kabzeel, Darius Benaya; Wijaya, Novia (E-Jurnal Akuntansi TSM, 2024)
The objective of this research is to obtain empirical evidence regarding the influence of profitability, liquidity, inventory intensity, related party debt, company size, leverage, and capital intensity on tax aggressiveness. This research utilizes a sample of all consumer non-cyclicals and consumer cyclicals companies listed on the Indonesia Stock Exchange during the period 2020-2022, with 66 consumer non-cyclicals and consumer cyclicals companies selected as the sample for this research. The sample selection employs the purposive sampling method with a total of 198 years of data, and the analysis is conducted using multiple linear regression. The results of this research showed that the profitability and company size variables have an influence on tax aggressiveness. The profitability (ROA) coefficient has a negative sign so it can be interpreted that profitability has a negative effect on the Effective Tax Rate (ETR). The results of this research show that the higher the Return on Assets (ROA) value produced by a company, the lower the company's ETR. The lower the ETR indicates the company is more aggressive, which means the higher the level of profitability, the higher the company's tax aggressiveness. Meanwhile, the liquidity, inventory intensity, related party debt, leverage, and capital intensity variables do not have an influence on tax aggressiveness.